Effects of Ligands on Unfolding of the Amyloid β-Peptide Central Helix: Mechanistic Insights from Molecular Dynamics Simulations - Ito, Mika; Johansson, Jan; Strömberg, Roger; Nilsson, Lennart (PLOS ONE, 2012)
Polymerization of the amyloid β-peptide (Aβ), a process which requires that the helical structure of Aβ unfolds beforehand, is suspected to cause neurodegeneration in Alzheimer's disease. According to recent experimental studies, stabilization of the Aβ central helix counteracts Aβ polymerization into toxic assemblies. The effects of two ligands (Dec-DETA and Pep1b), which were designed to bind to and stabilize the Aβ central helix, on unfolding of the Aβ central helix were investigated by molecular dynamics simulations. It was quantitatively demonstrated that the stability of the Aβ central helix is increased by both ligands, and more effectively by Pep1b than by Dec-DETA. In addition, it was shown that Dec-DETA forms parallel conformations with β-strand-like Aβ, whereas Pep1b does not and instead tends to bend unwound Aβ. The molecular dynamics results correlate well with previous experiments for these ligands, which suggest that the simulation method should be useful in predicting the effectiveness of novel ligands in stabilizing the Aβ central helix. Detailed Aβ structural changes upon loss of helicity in the presence of the ligands are also revealed, which gives further insight into which ligand may lead to which path subsequent to unwinding of the Aβ central helix.